PENGUMPULAN INFORMASI KEBUTUHAN BELAJAR PESERTA PELATIHAN PENDIDIKAN KECAKAPAN WIRAUSAHA DIGITAL MARKETING DI PKBM PELITA BANGSA - Yani, Dwi Artika; Ririn Gusti; Hutauruk, Lenni Mantili (IKIP Siliwangi, 2025)
This study aims to identify the learning needs information collection process carried out in the digital marketing entrepreneurship skills training at PKBM Pelita Bangsa, as well as how the data obtained can be used to improve the effectiveness of the training program as a whole. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation techniques. The results of the study indicate that the learning needs identification process was carried out by collecting secondary data information, especially from Google search engine pages and social media such as TikTok and Instagram. After that, primary data collection was carried out through interviews with training participants and information from registration forms.